Simple Renal Cysts as Markers of Thoracic Aortic Disease. Issue 1 (8th January 2016) - Ziganshin, Bulat A.; Theodoropoulos, Panagiotis; Salloum, Mohammad N.; Zaza, Khaled J.; Tranquilli, Maryann; Mojibian, Hamid R.; Dahl, Neera K.; Fang, Hai; Rizzo, John A.; Elefteriades, John A.
Abstract : Background: Thoracic aortic aneurysm is usually a clinically silent disease; timely detection is largely dependent upon identification of clinical markers of thoracic aortic disease (TAD); (bicuspid aortic valve, intracranial aortic aneurysm, bovine aortic arch, or positive family history). Recently, an association of simple renal cysts (SRC) with abdominal aortic aneurysm and aortic dissection was established. The aim of our study was to evaluate the prevalence of SRC in patients with TAD in order to assess whether the presence of SRC can be used as a predictor of TAD. Methods and Results: We evaluated the prevalence of SRC in 842 patients with TAD (64.0% males) treated at our institution from 2004 to 2013 and compared to a control group of patients (n=543; 56.2% males). Patients were divided into 4 groups: ascending aortic aneurysm (456; 54.2%); descending aortic aneurysm (86; 10.2%); type A aortic dissection (118; 14.0%); and type B aortic dissection (182; 21.6%). SRC were identified by abdominal computed tomography or magnetic resonance imaging of these patients. Prevalence of SRC is 37.5%, 57.0%, 44.1%, and 47.3% for patients with ascending aneurysm, descending aneurysm, type A dissection, and type B dissection, respectively. Prevalence of SRC in the control group was 15.3%. Prevalence of SRC was not significantly different between male and female aortic disease patients, despite reported general male predominance (2:1), which was also observed in our control group (1.7:1). Conclusions: This study establishes an increased prevalence of SRC in patients with TAD. SRC can potentially be used as a marker for timely detection of patients at risk of TAD.